FROM «SOFT» DECOLONIZATION TO DECOMMUNIZATION: ETHNOCENTRIC VISION OF THE CHANGE OF VERBAL MARKERS IN RIVNE PLACE NAMES SYSTEM - Долганов, П. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
This article concerns to the problem of analyzing decommunisation process in Ukraine which has been running since 2015. The process of renaming streets in regional perspective of Rivne town has been described in this exploration. This scientific research is composed of description the process of renaming streets which was led by local authorities, analyze of the political context of those decisions and explanation of theoretical approaches which is suitable for decommunisation exploring. This exploration was realized with using the transitional justice methodology as well as the concepts of ideological decolonization of the collective memory by Pierre Nora. The decommunisation process was described in this article mostly as artificial and politically instrumental practice that does not lead to the whole decolonization of collective memory. As a result we can come to conclusion that renaming streets is a part of decolonization (but not main), which is closed on postcolonial discourse and victimhood rhetoric. Further deep reordering of the totalitarian past in Ukraine needs more reflective approach to the ideological decolonization of common memory. Another serious problem is re indoctrination of urban memorial space by nationalistic symbols instead of soviet which was accompanying the decommunisation process. Radical nationalistic as well as military discourses became a bright dominant in renaming streets in Rivne.